The Ionospheric Bubble Index deduced from magnetic field and plasma observations onboard Swarm - Park, Jaeheung; Noja, Max; Stolle, Claudia; Lühr, Hermann (Earth, planets, and space, 2013)
In the post-sunset tropical ionospheric F-region plasma density often exhibits depletions, which are usually called equatorial plasma bubbles (EPBs). In this paper we give an overview of the Swarm Level 2 Ionospheric Bubble Index (IBI), which is a standard scientific data of the Swarm mission. This product called L2-IBI is generated from magnetic field and plasma observations onboard Swarm , and gives information as to whether a Swarm magnetic field observation is affected by EPBs. We validate the performance of the L2-IBI product by using magnetic field and plasma measurements from the CHAMP satellite, which provided observations similar to those of the Swarm . The L2-IBI product is of interest not only for ionospheric studies, but also for geomagnetic field modeling; modelers can de-select magnetic data which are affected by EPBs or other unphysical artifacts.